Cerebrospinal fluid biomarkers for Alzheimer’s disease: the role of apolipoprotein E genotype, age, and sex - Mehrabian S (Dove Medical Press, 2015)
Shima Mehrabian,1 Panagiotis Alexopoulos,2,3 Marion Ortner,2 Latchezar Traykov,1 Timo Grimmer,2 Alexander Kurz,2 Hans Förstl,2 Horst Bickel,2 Janine Diehl-Schmid21Department of Neurology, University Hospital “Alexandrovska”, Sofia, Bulgaria; 2Department of Psychiatry, Technische Universität München, Munich, Germany; 3Department of Psychiatry, University of Patras, Patras, GreeceIntroduction: Cerebrospinal fluid (CSF) biomarkers improve the diagnostic accuracy for Alzheimer’s disease (AD), even at the predementia stage of the disease. The ε4-allele of apolipoprotein E (ApoE ε4), female sex, and older age are well-known risk factors for AD. It is unclear how these risk factors affect the CSF biomarkers in patients with AD.Aim: The objective of this study was to investigate the associations of ApoE ε4, sex, and age with CSF biomarker levels in a unicenter sample of patients with AD that includes a high proportion of patients with early-onset AD (EOAD).Methods: The CSF levels of amyloid-β 1-42 (Aβ1-42) and total-tau of 117 subjects with mild to moderate AD (55 late-onset AD and 62 EOAD) were assessed. All subjects underwent ApoE genotyping, clinical evaluation, comprehensive neuropsychological assessments, and neuroimaging. Associations between CSF biomarker levels, ApoE ε4 allele frequency, age, and sex were evaluated.Results: In the whole patient sample and in the late-onset AD subgroup ε4 homozygous subjects had significantly lower CSF Aβ1-42 levels compared with ε4 heterozygous subjects and ε4 noncarriers. This association was not detected in the EOAD group. Age group, sex, and severity of cognitive decline did not have a significant impact on CSF Aβ1-42 levels. No significant associations were found between ApoE ε4 allele frequency and CSF total-tau levels.Conclusion: ApoE ε4 allele is associated with a reduction of CSF Aβ1-42 levels. This result is consistent with the findings of several previous studies. In the subgroup of patients with EOAD this association was not replicated. Larger studies are necessary to further investigate associations between ApoE ε4 allele frequency and CSF biomarker levels in patients with EOAD.Keywords: Alzheimer’s disease, biomarkers, CSF, Aβ1-42, ApoE, LOAD, EOAD, tau